Kewenangan Eksekusi Riil Pengadilan Negeri terhadap Perkara Konsinyasi Pengadaan Tanah Bagi Pembangunan untuk Kepentingan Umum - Simorangkir, Ronal Roges; Situmeang, Ampuan; Seroja, Triana Dewi (Universitas Batanghari Jambi, 2024)
Article 98 of the Government Regulation of the Republic of Indonesia Number 19 of 2021 concerning the Implementation of Land Acquisition for Development in the Public Interest states that in the event that compensation money has been entrusted to the District Court but the party is entitled to the land still controls the land object, execution can be requested, however The final product consignment application case is in the form of a determination and not a decision and the ruling is not condemnatory in nature, thus causing problems. This research is a normative juridical research that only examines primary, secondary and tertiary legal materials such as statutory regulations, both Law Number 48 of 2009 concerning Judicial Power and the Herzien Inlandsch Reglement (H.I.R) / Rechtreglement voor de Buitengewesten (Rbg), Republic of Indonesia Government Regulation Number 19 of 2021, Supreme Court Regulation Number 2 of 2021, books and journals. Data collection techniques using document study and analysis were carried out qualitatively, where the results of this research show that there is authority for the Chairman of the District Court to carry out real executions based on the Theory of Authority, Progressive Legal Theory and the Principle of Social Function, and in the future there must be reconstruction and harmonization of norms related to the execution of Land Acquisition consignment cases.